“El efecto de la urbanización en los niveles de pobreza: un estudio a nivel provincial en Ecuador durante el periodo 2010 al 2019” - Rentería Espinoza, Joel Adrián (2021)
Poverty is a serious problem that is reflected in the conditions and lack of resources of the most vulnerable households, even more so when the endowments between areas of the same region generate unfavorable conditions that exacerbate poverty. In this case, the main objective of this study was to evaluate the effect of urbanization on poverty levels at the provincial level in Ecuador during the period 2010 to 2019. For this purpose, a choice was made between a panel of fixed or random effects using the Hausman test, in addition, tests were applied to detect problems of heteroscedasticity and autocorrelation. Finally, generalized least squares (GLS) estimators were used, which corrected for the problems mentioned above. The results show that greater urbanization is negatively correlated with the poverty rate at the provincial level in the three study regions, with the eastern region having the greatest negative and significant effect of urbanization; on the other hand, this negative effect is preserved when control variables are included; with respect to the control variables, growth maintains a negative and significant effect on poverty, while unemployment has a positive effect on the poverty rate; this effect of the control variables is maintained only in the coastal and highland regions. Policy makers should expand social programs and public resources such as educational centers, medical facilities and agricultural production bonds; these mechanisms should be concentrated in rural areas with less integration to the cities, generating benefits similar to those offered in urban areas.